2009
DOI: 10.1136/jnnp.2008.170860
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured carotid artery aneurysms of the ophthalmic (C6) segment: clinical and angiographic long term follow-up of a multidisciplinary management strategy

Abstract: Based on favourable neuroradiological and ophthalmological outcomes, microsurgery is recommended for superiorly projecting aneurysms, especially aneurysms involving the ophthalmic artery, and for giant/large or wide necked aneurysms. Based on stable aneurysm occlusion and excellent clinical outcomes, embolisation can be recommended for inferiorly/medially projecting small, narrow necked aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 34 publications
3
24
0
1
Order By: Relevance
“…Under ICG videoangiography, real time blood flow vortices can be witnessed. Many papers have been published on surgery for paraclinoid aneurysms (2)(3)(4)6,7,9,(13)(14)(15)18). The mean age of the patients in these studies is 42-50 years and the SAH rate is 0-80.8%, with mostly large and giant but some small aneurysms, which are comparable to those in our study.…”
Section: Nagasawa Et Al (5)supporting
confidence: 87%
See 1 more Smart Citation
“…Under ICG videoangiography, real time blood flow vortices can be witnessed. Many papers have been published on surgery for paraclinoid aneurysms (2)(3)(4)6,7,9,(13)(14)(15)18). The mean age of the patients in these studies is 42-50 years and the SAH rate is 0-80.8%, with mostly large and giant but some small aneurysms, which are comparable to those in our study.…”
Section: Nagasawa Et Al (5)supporting
confidence: 87%
“…Combined with the use of near-infrared video technology in current microscopes, surgeons can evaluate intraoperative blood flow with a simple intravenous injection. Previous studies have reported its use in cerebral arteriovenous malformations, aneurysms, and extracranial-intracranial bypasses with good results (12)(13)(14)(15)(16)(17). This study is dedicated to present our experience with the use of ICG videoangiography in surgical clipping of paraclinoid aneurysm.…”
Section: Introductionmentioning
confidence: 99%
“…Many papers have been published on surgery for paraclinoid (ophthalmic segment) aneurysms 2,3,6,[11][12][13][14][15][16][17] . They report mortality rates varying from 0 to 13.8% and morbidity up to 26.8%.…”
Section: Outcomes Of Surgical Treatmentmentioning
confidence: 99%
“…12 We used standard embolization techniques with Guglielmi detachable coils (Boston Scientific, Natick, Massachusetts), including soft and 3D coil constructs.…”
Section: Methodsmentioning
confidence: 99%